Developing Operational Performance Through Customer Engagement, e-Ticketing and Customer Satisfaction: a Mediation Perspective - Pratama, Agung Satrya Adi; Nusraningrum, Dewi (ARE Publisher, 2025)
Objectives: this study aims to explore the role of customer satisfaction as a mediator for the influence of customer engagement and e-ticketing on operational performance.Methodology: This study uses a causal design with a survey method conducted by distributing Likert scale questionnaires: customer engagement, e-ticketing, customer satisfaction, and operational performance to 170 service users (ship passengers) at Merak Port. Data analysis using structural equation modeling based on partial least squares (SEM-PLS) supported by descriptive and correlational analysis.Findings: The results showed that customer engagement, e-ticketing, and customer satisfaction have a significant effect on port operational performance; customer engagement and e-ticketing have a significant effect on ship passenger customer satisfaction, and customer satisfaction mediates the effect of customer engagement and e-ticketing on port operational performance.Conclusion: The model's novelty of the effect of customer engagement and e-ticketing on port operational performance with customer satisfaction mediation. This model deserves critical and in-depth discussion before being adopted or adapted by researchers and practitioners in the future.